1999
DOI: 10.1021/la9803068
|View full text |Cite
|
Sign up to set email alerts
|

Structural Modifications of DMPC Vesicles upon Interaction with Poly(amidoamine) Dendrimers Studied by CW-Electron Paramagnetic Resonance and Electron Spin−Echo Techniques

Abstract: This report describes a computer-aided CW- and pulsed-electron paramagnetic resonance (EPR) investigation on the structural modification of dimyristoylphosphatidylcoline (DMPC) vesicles, which occur upon interaction with starburst dendrimers (SBDs). Probes used for this study included doxyl-functionalized stearic acids, with the doxyl group attached at different positions of the stearic chain (5DXSA, 12DXSA, and 16DXSA). Mainly mobility and polarity parameters were evaluated from the analysis of the CW-EPR spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
69
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 44 publications
(46 reference statements)
5
69
0
3
Order By: Relevance
“…Thus, anionic liposomes in the absence of NaCl are approximately 5 nm larger than those prepared in a salty environment ( Table 2). Similar to other interaction studies of dendrimer against liposomes [28,45,46], we observed that the presence of various PPIs in solution influences the hydrodynamic diameter of liposomes. Hydrodynamic diameter of neutral DMPC liposomes increases after the addition of pure PPI to the liposome solution (Table 2), while no (pure Hepes buffer) or nominal (Hepes buffer with NaCl) increase of neutral liposomes' diameter in the presence of OS PPI and DS PPI is recognizable.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Thus, anionic liposomes in the absence of NaCl are approximately 5 nm larger than those prepared in a salty environment ( Table 2). Similar to other interaction studies of dendrimer against liposomes [28,45,46], we observed that the presence of various PPIs in solution influences the hydrodynamic diameter of liposomes. Hydrodynamic diameter of neutral DMPC liposomes increases after the addition of pure PPI to the liposome solution (Table 2), while no (pure Hepes buffer) or nominal (Hepes buffer with NaCl) increase of neutral liposomes' diameter in the presence of OS PPI and DS PPI is recognizable.…”
Section: Discussionsupporting
confidence: 89%
“…The number of surface groups, their charge and the shapes of molecules affect the strength of interaction. Higher generations of dendrimers affect the structure of the lipid bilayer triggered by number of cationic surface groups [27,45,46]. In the present work, we used cationic unmodified PPI dendrimer and cationic open shell PPI glycodendrimer, but also a neutral dense shell glycodendrimer to investigate their interaction with model lipid membranes.…”
Section: Discussionmentioning
confidence: 99%
“…The dendrimer -vesicle interactions are dependent on the membrane composition (e.g., are weak for vesicles that contain a high fraction of PC and are strong for PE-containing vesicles). There are also studies postulating that the integrity of DMPC vesicles upon contact with PAMAM G7 dendrimers is maintained, although there are changes in ordering of the bilayer and rotational mobility of fatty acid chains [9]. The bilayer couple hypothesis explains echinocytic transformation as an effect of an asymmetric expansion of one monolayer [10].…”
Section: Resultsmentioning
confidence: 99%
“…3). Interactions between dendrimers and the lipid bilayer have been studied using many methods such as EPR techniques [26][27][28], leakage, lipid mixing and content mixing assays [29][30][31], differential scanning calorimetry [32,33], and atomic force microscopy [34]. Loss of integrity of the RBC membrane which may occur under the influence of dendrimers is accompanied by haemoglobin leakage, which can be measured.…”
Section: Generationmentioning
confidence: 99%